Difference in speed at fixed reference points, and changes in speed between fixed reference points, during 100 meter swimming races at the European Championships, 2010. Manuscript and coaching applications - Buhre, T. (Journal of Swimming Research, 2016)
The purpose was to examine the differences and relationships between speed variables and performance in 100 meter events at the European Championships long course (LC) and short course (SC) for all strokes and gender. Data was collected from the website www.swim.ee, transformed, and analyzed using statistical methods. Swimming speed (SS) at different reference points was significantly different for in both short course (SC) and long course (LC) swimming, SS15>SS35>SS45<SS65>SS85>SS95. The effect size for all measures was large (Cohen's d). The changes in SS between reference points was significantly different in all events for both sexes in both SC and LC swimming, DeltaSS15:35> DeltaSS35:45, but only for SC when comparing DeltaSS85:95> DeltaSS65:85. Correlations of placing at the end of the race, split times for each 50 m segment and SS at different reference points, showed no clear pattern. The differences in the swimming speed variables, can be explained based on the theory of complexity and performance, utilizing previous research findings and the standard equation of drag force in fluids. Thus taking into account all different aspects of performance. The managing of speed through out a race needs to be a special focus in both training and competition. Thus, allowing for a more individualized approach both in utilizing training methods training and analysis of performance in 100 m race.